Challenging private law Lord Sumption on the Supreme Court - Worthington, Sarah 1955-; Day, William (Hart, 2020)
"Lord Sumption has been one of the most influential judges of his generation. This book critically reflects on the important and controversial issues posed by his jurisprudence. Using Lord Sumption's contributions as a springboard, the book contains a selection of essays that consider 'where next' in relation to topics such as: - contractual interpretation; - tortious duties of care; - compensatory damages; - proprietary restitution; - piercing the corporate veil. The book covers a broad range of areas in private law including contract, tort, unjust enrichments, equity, company and commercial law, as well as private international law and civil procedure"--
"This book of essays is the product of a two-day legal conference held under the auspices of the Cambridge Private Law Centre in October 2019."
Keywords: Sumption, Jonathan -- 1948-; Großbritannien -- Supreme Court; Bürgerliches Recht; Internationales Privatrecht; Sumption, Jonathan; Great Britain / Supreme Court; Great Britain / Supreme Court / Officials and employees; Civil law / England; Judicial opinions / England; Conflict of laws / England; Aufsatzsammlung; Konferenzschrift